Procurement of electric multiple-unit trains [Tender documents : T26268051] (MENA Report, 2015)
The client intends to participate in the tender for the provision of rail services for the Stuttgart network 1 (Lots 1 to 3), which was published in the EU Official Journal under no. 2014 / S 124-220981. In the event that the Client is awarded to one or more items from these tender, it needs required for the provision of transport services number of electric multiple units and possibly related services such. Ie repair and maintenance and provision of a workshop. The procurement of electric multiple units and possibly associated services is the subject of this tender.